On the Question of SCO Bank Institutionalisation - Ksenia Gennadyevna Muratshina (Управленческое консультирование)
This paper is aimed at the analysis of the institutionalization of financial organ in the framework of the Shanghai Cooperation Organization. The paper outlines such aspects as: historical background and basic stages of SCO Bank concept development, correlation of SCO Bank concept with the general view of China’s economic strategy in Central Asia and the two alternatives of SCO financial institution - namely SCO Development Bank and SCO Foundation. The first one is promoted by the People’s Republic of China, while the second one was put forward by the Russian Federation. For China, SCO Bank formation according to Beijing-led principles would bring considerable benefits in terms of interest rates and contribute to its influence in Central Asia. Meanwhile, the post-Soviet Central Asian states are also advocating the Chinese plan of the Bank, due to the fact that almost all of them are interested in acquiring more and more lending from outside. In this situation, Russia ought to make an urgent decision, whether it should stand for its proposal of SCO Foundation or elaborate new initiatives. Economic cooperation has already become an important aspect of SCO multilateral interaction, and for Russia in these circumstances the most essential objective to realize would be the elaboration of a consistent strategy and the maintenance of its own priorities in Eurasian integration.